Research of the master–slave robot surgical system with the function of force feedback. Issue 4 (17th May 2017) - Shi, Yunyong; Zhou, Chaozheng; Xie, Le; Chen, Yongjun; Jiang, Jun; Zhang, Zhenfeng; Deng, Ze
Abstract: Background: Surgical robots lack force feedback, which may lead to operation errors. In order to improve surgical outcomes, this research developed a new master–slave surgical robot, which was designed with an integrated force sensor. Methods: The new structure designed for the master–slave robot employs a force feedback mechanism. A six‐dimensional force sensor was mounted on the tip of the slave robot's actuator. Sliding model control was adopted to control the slave robot. According to the movement of the master system manipulated by the surgeon, the slave's movement and the force feedback function were validated. Results: The motion was completed, the standard deviation was calculated, and the force data were detected. Hence, force feedback was realized in the experiment. Conclusions: The surgical robot can help surgeons to complete trajectory motions with haptic sensation.